Buffer-stock saving in a Krusell-Smith world - Christopher D. Carroll; Jiri Slacalek; Kiichi Tokuoka (European Central Bank (ECB), 2014)
A large body of microeconomic evidence supports Friedman (1957)'s proposition that household income can be reasonably well described as having both transitory and permanent components. We show how to modify the widely-used macroeconomic model of Krusell and Smith (1998) to accommodate such a microeconomic income process. Our incorporation of substantial permanent income shocks helps our model to explain a substantial part of the large degree of empirical wealth heterogeneity that is unexplained in the baseline Krusell and Smith (1998) model, even without heterogeneity in preferences.
Keywords: D12; D31; D91; E21; 330; aggregate uncertainty; household income process; wealth inequality